Strategic decisions in transport: a case study for a naval base selection in Brazil - Caruzzo, Amaury; Barros Cardoso, Priscila Renata; Vieira Junior, Hélcio; Belderrain, Mischel Carmen Neyra (Transportes, 2016)
A decision on a military strategic environment, such as the selection of a new naval base, is a complex process and involves various criteria. In this context, few studies are available on the problems of military-naval transport decisions. Therefore, the aim of this paper is to present a maritime transport case study using a multi-methodology framework in a process of strategic decision making in logistics. Through a review of the literature, normative documents from the Brazilian armed forces, and interviews with military officers, criteria and preferences were identified and a hierarchical structure was constructed for a case study in the Brazilian Navy–the location of the second Fleet Headquarters. The results indicated that São Marcos Bay, in Maranhão State, was the best location among the alternatives. The multi-criteria approach was shown to be a valuable tool in assisting the decision making process and to understand the trade-offs between strategic and operational criteria in a transport decision.